2005
DOI: 10.1073/pnas.0409920102
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification and strain-typing of respiratory pathogens for epidemic surveillance

Abstract: Epidemic respiratory infections are responsible for extensive morbidity and mortality within both military and civilian populations. We describe a high-throughput method to simultaneously identify and genotype species of bacteria from complex mixtures in respiratory samples. The process uses electrospray ionization mass spectrometry and base composition analysis of PCR amplification products from highly conserved genomic regions to identify and determine the relative quantity of pathogenic bacteria present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
151
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(153 citation statements)
references
References 20 publications
1
151
0
1
Order By: Relevance
“…The data are consistent with previous reports suggesting that only a small number of the known emm types are generally associated with high virulence and invasive characteristics, with M1, M3 and M5 foremost among them. 3,6,10,14,15,18,23,24 In much the same way that the rise and fall of M75 appears responsible for recent spikes in macrolide resistance, the data suggest that the observed spikes in GAS-associated ARD and invasive disease were associated with the shifting dominance of a particularly virulent strain, M5. The association between this serotype and the widespread rate increases seen among trainees from 2002 through 2007 supports the general hypothesis that virulence is strongly linked to serotype.…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…The data are consistent with previous reports suggesting that only a small number of the known emm types are generally associated with high virulence and invasive characteristics, with M1, M3 and M5 foremost among them. 3,6,10,14,15,18,23,24 In much the same way that the rise and fall of M75 appears responsible for recent spikes in macrolide resistance, the data suggest that the observed spikes in GAS-associated ARD and invasive disease were associated with the shifting dominance of a particularly virulent strain, M5. The association between this serotype and the widespread rate increases seen among trainees from 2002 through 2007 supports the general hypothesis that virulence is strongly linked to serotype.…”
Section: Methodsmentioning
confidence: 81%
“…The most common method of direct serological identification is M typing, 16 but this has been widely replaced by inference of M type from emm gene sequence analysis, 17 or more indirectly inferred by various forms of multilocus sequence typing. 18 All of these methods have shown broad concordance to the degree that they overlap in coverage. 19 Analysis of the sample set collected for this study showed very strong correlations between emm type and antibiotic resistance phenotypes, as well as strong tendencies for specific types to be associated with outbreaks.…”
Section: Molecular Epidemiology Of Gas Among Military Recruitsmentioning
confidence: 99%
“…Samples 2, 8, 10, and 19 contained variant T8993G, sample 15 contained T8993C, and sample 12 contained G11778A. Samples 3,5,7,9,11,13,14,16,17,18,20, and 21 lacked any of the 7 pathogenic mutations.…”
Section: Ms Detection Of Snps In Mtdnamentioning
confidence: 99%
“…Recently, MS-based nucleic acid protocols have migrated out of MS labs for application in other disciplines, including human and microbial forensics, drug discovery, infectious-disease diagnostics, and biological warfare agent detection (6)(7)(8)(9)(10). Because the masses of the 4 mononucleotides (dAMP, dTMP, dGMP, and dCMP) comprising DNA are known with great accuracy, highly precise measurements of mass can be used to derive a base composition (or a constrained list of base compositions).…”
mentioning
confidence: 99%
“…Two promising techniques, real-time PCR and mass spectrometry, target genetic information at different levels: DNA and proteins. The polymerase chain reaction (PCR) has demonstrated unparalleled levels of sensitivity and specificity by targeting DNA for amplification [5][6][7]. Unfortunately, the time required for the PCR reaction hinders rapid detection [5][6][7].…”
mentioning
confidence: 99%